Espaço público como palco das manifestações coletivas e da vitalidade urbana: subversão à ordem, luta pelo direito à cidade e expressão dos conflitos urbanos de Belo Horizonte - Karina Machado de Castro Simão (2020)
The city results from historical and social processes over time. Its main function, according to Lefebvre (2008), is urban life, which occurs mainly in public space, when use value predominates over exchange value. Starting from capitalism and accentuated by neoliberalism, exchange value has predominated and urban space is produced by a hegemonic class and a order, intensifying social contradictions and urban conflicts. Urban conflicts express the discontent of society, revealing itself from collective manifestations, which happen mainly in the public space. Collective manifestations are a form of subversion to order and the struggle for the right to the city, which aims to transform urban life. It is worth highlighting the importance of urban conflicts, which contribute to urban vitality and to the reading of the city, thus providing subsidies for the elaboration of urban planning and democratic public policies.The work starts from the hypothesis that the ordering of urban space and society implies a paradox: the reaction to the imposed order is its own questioning. The objective of the thesis is to investigate the public space of Belo Horizonte as the place of subversion to the hegemonic order, of fighting for the right to the city and of manifestation of urban conflicts. The collective manifestations that express urban conflicts and that occur, above all, in Sete de Setembro Square, Estação Square and Liberdade Square are studied. The methodological procedures adopted deal with qualitative and exploratory research, based on theoretical and bibliographic review and documentary research. Belo Horizonte's urban conflicts, expressed by collective manifestations, are analyzed from the data collection of Belo Horizonte Urban Conflict Observatory. When analyzing the historical trajectory and the collective manifestations performed in the squares, it is understood that Sete Square and Estação Square are places of public and political character, of the party, of urban vitality, of subversion to order, of the struggle for the right to city and the expression of urban conflicts. However, Liberdade Square, a symbol of state power, represents an orderly space, where the public character is selective and, often, excluding. However, it is still the place for the expression of countless conflicts, revealing other desires for the city. The collective manifestations that took place in Belo Horizonte, especially in Sete de Setembro Square and Estação Square, confirm the hypothesis of the work that the ordering of space and urban society implies the contestation of the order itself. To deny conflicts is to deny urban vitality and disregard the multiple possibilities of, based on its understanding, allowing the search for urban transformation, aimed at building a democratic and inclusive city, in which the right to the city is not limited to rhetoric.